2007
DOI: 10.1056/nejmoa060357
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Duties and Deaths from Heart Disease among Firefighters in the United States

Abstract: BackgroundHeart disease causes 45% of the deaths that occur among U.S. firefighters while they are on duty. We examined duty-specific risks of death from coronary heart disease among on-duty U.S. firefighters from 1994 to 2004. MethodsWe reviewed summaries provided by the Federal Emergency Management Agency of the deaths of all on-duty firefighters between 1994 and 2004, except for deaths associated with the September 11, 2001, terrorist attacks. Estimates of the proportions of time spent by firefighters each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
461
2
15

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 523 publications
(496 citation statements)
references
References 29 publications
9
461
2
15
Order By: Relevance
“…Their episodic intense work, combined with those health risks, contribute to myocardial infarctions being the leading cause of on duty death [9]. Healthy lifestyles are of additional importance because firefighters' risk of cancer is increased [10].…”
Section: Discussionmentioning
confidence: 99%
“…Their episodic intense work, combined with those health risks, contribute to myocardial infarctions being the leading cause of on duty death [9]. Healthy lifestyles are of additional importance because firefighters' risk of cancer is increased [10].…”
Section: Discussionmentioning
confidence: 99%
“…Prior research has identified occupational16, 17 and individual5, 6, 12 factors associated with an increased risk of cardiac death in the fire service. Careful analysis of autopsy data offer the opportunity to better understand the underlying pathoanatomic features associated with SCD.…”
Section: Introductionmentioning
confidence: 99%
“…The combination of cardiovascular, thermal and psychological stresses which are routinely experienced may trigger cardiac events. Fire suppression activities increase the risk of suffering from a cardiac event by 10-100 times compared to non-firefighting duties (Kales et al 2007). This risk is further exacerbated by underlying health issues, such as obesity and hypertension (Kales 2007, Kales 2009, Geibe et al 2008.…”
Section: Introductionmentioning
confidence: 99%
“…Fire suppression activities increase the risk of suffering from a cardiac event by 10-100 times compared to non-firefighting duties (Kales et al 2007). This risk is further exacerbated by underlying health issues, such as obesity and hypertension (Kales 2007, Kales 2009, Geibe et al 2008. The high incidence of myocardial infarction makes cardiac strain experienced by firefighters a major concern Yang et al 2013).…”
Section: Introductionmentioning
confidence: 99%